Mother, Child and Community in Rural Malawi: Security-Seeking Behaviour and the Role of Under-Five Clinics - Rosenthal, Anat (Anthropologica, 2015)
Health care delivery has emerged as a major challenge in global health. Despite unprecedented advances in medicine, as well as significant financial investments, innovations in health have yet to reach most of the world's population. Under-Five Clinics in rural Malawi offer a window onto how rural African communities are responding to new initiatives in health care. This article claims that participation in Under-Five Clinics is part of a broader social process of security-seeking behaviour in which individuals work to improve their sense of human security in an environment of extreme poverty, lack of adequate employment and limited access to health care services.